Potencialidades Turísticas que presenta el sector de campiña de Moche, distrito de Moche, provincia de Trujillo, región La Libertad, para la práctica del agroturismo. - Villanueva Padilla, Dany Yack (2017)
This investigation treats brings over of the tourist potentials that the sector presents_x000D_ Moche's Field, Moche's district, province of Trujillo, for for the practice of the_x000D_ agrotourism. Therefore he has identified to the traditional cultures as: the maize,_x000D_ the yucca, the yam; the alfalfa like tourist potentials in the above mentioned sector,_x000D_ likewise the obtained products use as inputs for the gastronomy, other one of the_x000D_ tourist potentials that one presents is the hospitable attitude of the farmer opposite_x000D_ to the tourist, who manages to visit his agricultural plots, and is where the social_x000D_ interrelationship takes place, during this context the farmer teaches them his_x000D_ agricultural daily labors learned of his forbears, which use as information to work_x000D_ the land and to obtain the traditional cultures of the maize, yucca, yam and alfalfa,_x000D_ which possess a great cultural value in the daily life of the farmer mochero._x000D_ Also he has identified as other one of the tourist potentials, to the road_x000D_ accessibility, which performs supreme importance, inside the tourist activity since_x000D_ into her the access relapses, the viability of Moche's Field - city of Trujillo comes to_x000D_ the sector and vice versa, in the same way this access appears of Moche's Field to_x000D_ the agricultural plots, where they find the traditional cultures. All the necessary_x000D_ already mentioned potentials are important in order that the practice of the_x000D_ agrotourism gives in the sector Moche's Field, as new tourist alternative, in the_x000D_ possession of new experiences to the tourist._x000D_ The scientific used methods were: the ethnographic method, analytical method -_x000D_ synthetic; the technologies of: the direct observation, the graphical record, the_x000D_ signing, the interview, and the survey; and the instruments as: Passbook of Field,_x000D_ Digital Camera, the card of observation - test of behavior, the questionnaire of_x000D_ interview, and the Questionnaire of Survey._x000D_ In order that the destination of Sector Field of Moche-Trujillo continues developing_x000D_ turísticamente in the aspect agroturistico it is necessary to stimulate in the farmers'_x000D_ community, to take part in the tourist fairs and gastronomic national festivals and_x000D_ internationally._x000D_ The Author